Subcellular trafficking and post-translational modification regulate PIN polarity in plants - Cheng, Shuyang; Wang, Yizhou (Frontiers in Plant Science, 2022)
Auxin regulates plant growth and tropism response. As a phytohormone, auxin is transported between its synthesis sites and action sites. Most natural auxin moves between cells via a polar transport system which is mediated by PIN-FORMED (PIN) auxin exporters. PIN proteins are asymmetrically localized within cells to determine the directionality of intercellular auxin flow. Different internal cues and external stimuli can modulate PIN polar distribution and activity through multiple levels, including transcription, protein stability, subcellular trafficking and post-translational modification, and thus regulate auxin-distribution-dependent development. Thus, there is a complicated network in the different regulation levels of PINs polarity. For example, the post-translational modification of PINs can affect the subcellular trafficking factors. In this review, we will focus on subcellular trafficking and post-translational modification of PINs to summarize the recent understanding of PINs polarity.